Interfacial Effects of UV-Ozone Treated Sol-Gel Processable ZnO for Hybrid Photodetectors and Thin Film Transistors. (2019) - Pickett, Alec; Mohapatra, Aiswarya A.; Ray, Suman; Robledo, Christopher; Ghosh, Kartik; Patil, Satish; Guha, Suchismita
ABSTRACT: Hybrid organic-inorganic semiconducting interfaces have attracted attention in photodiodes and field-effect transistors (FETs) due to the realization of intrinsic p-n junctions and their mechanical flexibility. With the difficulty of developing high-mobility n-type organic semiconductors due to the necessity of low LUMO levels and ambient environment stability, solution processable inorganic materials are an excellent alternative. ZnO is an intrinsic n-type semiconductor which is non-toxic and sol-gel processable, creating avenues for film patterning and fully solution processed devices. We report the improvement of electron mobilities in ZnO FETs through simple UV-Ozone processing which reduces lattice defects within the film and at the SiO2 /ZnO interface. Treated ZnO films yield electron mobilities close to 10 -2 cm 2 /Vs and on/off current ratios of 10 4 while non-treated films have mobilities on the order of 10 -5 cm 2 /Vs and an order of magnitude lower on/off current ratios. Treated films also yield improved photoresponsivity and detectivity in hybrid ZnO-organic photodetectors.